Protocol for cryopreserving neural organoids and human living brain tissue using MEDY - Weiwei Xue; Jiacheng Du; Yunteng Li; Zhicheng Shao (STAR Protocols, 2024)
Summary: Cryopreservation of neural organoids and human living brain tissue faces huge challenges. Here, we present a cryopreservation protocol for the reliable storage of diverse neural organoids and human living brain tissue using methylcellulose, ethylene glycol, DMSO, and Y27632, termed MEDY. We describe steps for preparing cryopreservation solution, preparing cortical organoids, and surgical removal of human brain tissue. We then detail procedures for cryopreservation, resuscitation, and detection assays. This protocol can serve as a model for studying human neurological diseases.For complete details on the use and execution of this protocol, please refer to Xue et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.